2021
DOI: 10.1590/1413-812320212612.35842020
|View full text |Cite
|
Sign up to set email alerts
|

Desconhecimento sobre a campanha de vacinação contra o HPV entre estudantes brasileiros: uma análise multinível

Abstract: Resumo O objetivo deste artigo é analisar a associação entre o desconhecimento sobre a campanha de vacinação contra o HPV entre adolescentes e fatores individuais e contextuais. Estudo transversal com dados da Pesquisa Nacional de Saúde do Escolar (2015). Foi realizada a análise bivariada e calculadas as Razões de Prevalência em uma Regressão de Poisson multinível (IC95%) para verificar o efeito das variáveis no desfecho. O desfecho esteve associado significativamente a ter 15-19 anos de idade (RP=1,36), estud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0
15

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(35 citation statements)
references
References 16 publications
(22 reference statements)
2
13
0
15
Order By: Relevance
“…The unawareness of HPV vaccination was the most frequent reason among those listed to justify non-vaccination by schoolchildren. This result was also reported by a study with data from PeNSE 2015, revealing that 10.30% of the students did not know or had not heard of the HPV vaccination campaign 5 . The same study found a positive association between the unawareness of the campaign against HPV and the age group from 15 to 17 years, studying in the afternoon/night shift, having had sex, presenting self-perception of health status as poor or very poor, being dissatisfied or indifferent about body image, and studying in public school 5 .…”
Section: Discussionsupporting
confidence: 74%
See 4 more Smart Citations
“…The unawareness of HPV vaccination was the most frequent reason among those listed to justify non-vaccination by schoolchildren. This result was also reported by a study with data from PeNSE 2015, revealing that 10.30% of the students did not know or had not heard of the HPV vaccination campaign 5 . The same study found a positive association between the unawareness of the campaign against HPV and the age group from 15 to 17 years, studying in the afternoon/night shift, having had sex, presenting self-perception of health status as poor or very poor, being dissatisfied or indifferent about body image, and studying in public school 5 .…”
Section: Discussionsupporting
confidence: 74%
“…Considering that an analysis by sex is essential for the proper evaluation of health indicators in Brazil and that the results of our study showed a lower proportion of male adolescents vaccinated against HPV compared to females in all regions of the country, interventions should consider gender differences when developing health strategies aimed at improving immunization indicators in this group. A study with data from PeNSE 2015 also showed a higher proportion of unvaccinated male adolescents and a positive association between males and unawareness of the HPV campaign 5 .…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations